Ephemera of a Promised Land: Two Travel Guides in a Reconstituted Jerusalemite Family Archive - Micaela Sahhar (Mashriq & Mahjar, 2023)
This article investigates Christian Palestinian involvement in tourism and Western pilgrimage in Mandate Palestine, and focuses on the tension between political identity and mercantile aspirations. It makes use of an ephemeral archive that highlights the possibilities of reconstructing a picture of Mandate-era Jerusalem based on such transient documents. The article examines two 1930s travel pamphlets, published in English and co-authored or co-edited by a Greek-Orthodox Jerusalemite, George M. Sahhar (1901–1976). Sahhar tourism enterprises in Jerusalem catered to an English-speaking British and American clientele, some associated with the British-Israelite movement. Both guides offer insight into Christian tour operators and the tastes of their clientele and indicate Western appetite for biblical and pseudo-historical narratives of Jewish connections to Palestine. Together, they illustrate the ambivalent instrumentality of Christian Palestinian entrepreneurs in biblifying Palestine for the Western imaginary and even propagating ideas of Palestinian progress as facilitated by Zionist modernity, a strategy now implicated in normalizing Israel’s 1948 creation and later deployed in Israeli national narratives.